CYTOTOXIC ACTIVITIES PROFILE OF PARASITE MANGO (Dendrophthoe pentandra) FROM VARIOUS AREAS IN INDONESIA AGAINST T47D BREAST CANCER CELLS AND NORMAL VERO CELL LINES - Mutiah, Roihatul (Journal of Islamic Pharmacy, 2019)
Indonesia has so many kinds of a parasite (mistletoe), one of them which has potential anticancer activity is mango parasite (Dendrophthoe pentandra). This research aimed at determining the cytotoxic activity profile of mango parasite leaves extracts from several locations in Indonesia against T47D and Vero cell lines. Mango parasite leaves obtained from 4 locations in Indonesia: Kediri, Pekalongan, Sumatra, and Kalimantan. Three samples was obtained from 3 different sub-districts in each locations. Cytotoxic activities of samples were performed by MTT assay method. The results of this study showed that there were differences between samples obtained from different locations, especially in cytotoxic activity and selectivity indexes of mango parasite leaves (D. pentandra) ethanol extract. D. pentandra obtained from Kalimantan has the most potential cytotoxic activity and could be potentially developed into a T47D breast anticancer agent. Extracts from the Kalimantan have an IC50 values of287.39 Î¼g/ml, LC50 798.28 Î¼g / ml and selectivity index 2.77, which means it was toxic to cancer cells but safe for Vero cell lines, and its selectively kills cancer cells rather than Vero cell lines. The result of this study could support D. pentandra to be developed as a new potential Fitofarmaka.